Overstaying of students in the Division of Social Sciences, College of Arts and Sciences, University of the Philippines in the Visayas during the second semester 1991-1992. - Endonila, Arlie Jo B. (1992.)
This descriptive study was conducted to identify the reasons attributed to overstaying by students in the Division of Social Sciences, College of Arts and Sciences, University of the Philippines in the Visayas. Data were taken from 40 respondents who have exceeded eight semesters of residence in UP and have enrolled or are in residence during the second semester of the school year 1991-92. The respondents were given questionnaires to be filled out. The results were tabulated and analyzed in terms of frequencies and percentages. The results of the study showed two categories of reasons for overstaying. These reasons are Academic Related Reasons and Non-Academic Related Reasons. Academic Related Reasons include 1)Deficiency in thesis requirement, 2)Failure in subject, 3)Deficient subject offerings, 4)Shifting, and 5)Teacher factor. Non-Academic Reasons include 1)Personal/Psychological problems, 2)Financial difficulties, 3)Physical illness, 4)Involvement with other activities, and 5)Lack of determination on the part of the student to graduate on time. It is significant to note that when compared with the areas of specialization, length of overstaying or gender, the Academic-Related Reasons with the highest frequency is failure in subjects. Likewise, for the Non-Academic Related Reasons for overstaying, personal/psychological problems rank highest in frequency even when compared as to area of specialization, length of overstaying and gender. Majority of those who incurred failing grades also had personal/psychological problems.
Thesis (Undergraduate, Bachelor of Arts in Social Sciences) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Students -- Overstaying